PENGARUH PEMASARAN DIGITAL DALAM MENINGKATKAN PENJUALAN PRODUK SPART PART KOMPUTER MELALUI TIK TOK DI KOTA PADANG - Agus Nurofik; Nini Nini; Hendrik Permana; Tri Irfa Indrayani (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
With the rapid growth of e-commerce in Indonesia, TikTok in Padang is the platform most widely used by potential customers to introduce their products, including computer spare parts, especially to young consumers active on digital platforms like TikTok. Computer spare parts serve as a means of repairing computer problems and offer significant potential for online sales due to high demand across all segments of society. This study aims to analyze the online marketing tactics entrepreneurs use through TikTok to increase sales of computer spare parts in Padang City. The researchers employed a descriptive qualitative approach and collected data through direct observation, interviews, and documentation. The results show that TikTok serves as a highly effective promotional tool for attracting customers, primarily due to its engaging content, collaboration with local influencers, and active interaction with followers. Furthermore, features such as Stories and Reels, as well as paid advertising, contribute to expanding promotional reach. Entrepreneurs in Padang City have successfully increased sales volume and developed their products through the implementation of sustainable content strategies and a deep understanding of market needs.